2019
DOI: 10.1093/ndt/gfz115
|View full text |Cite
|
Sign up to set email alerts
|

High-protein diet with renal hyperfiltration is associated with rapid decline rate of renal function: a community-based prospective cohort study

Abstract: Background The effect of a high-protein diet with renal hyperfiltration (RHF) on decline of kidney function has rarely been explored. We investigated the association between a high-protein diet, RHF and declining kidney function. Methods A total of 9226 subjects from the Korean Genome and Epidemiology Study, a community-based prospective study (2001–14), were enrolled and classified into quartiles according to daily amount of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 35 publications
4
46
1
Order By: Relevance
“…Although not observed in this study, an association between high protein intake and elevated eGFR has been reported in several studies [7,37]. This discrepancy might be caused by a difference in glomerular hyperfiltration between the single-nephron level and the whole-kidney level [5].…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Although not observed in this study, an association between high protein intake and elevated eGFR has been reported in several studies [7,37]. This discrepancy might be caused by a difference in glomerular hyperfiltration between the single-nephron level and the whole-kidney level [5].…”
Section: Discussioncontrasting
confidence: 70%
“…In animal models [3,4] and humans [5,6], dietary protein was shown to increase intrinsic acid production, which can cause kidney injury due to acid retention-induced kidney endothelin and aldosterone production. Furthermore, increased dietary protein per se was shown to induce kidney injury through a hemodynamic mechanism of renal hyperfiltration in humans [7] and experimental animals [8]. However, the direct association between protein intake and glomerular hemodynamic response remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“… 30 , 31 , 32 , 33 For example, adherence to a healthy plant-based diet (fruits, vegetables, whole grains, nuts, and legumes) was associated with lower risk for developing CKD, 30 , 31 whereas a higher animal-based protein intake was associated with increased risk for kidney hyperfiltration and rapid kidney function decline. 34 Similarly, a Mediterranean-style diet (ie, high in fruits and vegetables) was associated with lower risk for incident loss of kidney function (estimated glomerular filtration rate [eGFR] < 60 mL/min per 1.73 m 2 ). 32 Although red meat intake is strongly associated with increased risk for kidney failure in the general population, substituting 1 daily serving of red meat with another source of protein was shown to reduce the risk for kidney failure by 62% (for poultry), 50% (for soy, legumes, or eggs), or 49% (for fish).…”
Section: Potential Benefits Of a Plant-based Dietmentioning
confidence: 99%
“…Our study presents several limitations. First, we excluded patients with renal and hepatic diseases, and therefore the safety of a high-protein diet for these patients must be assessed because of its potential effects on renal function [29,35]. Second, although we asked patients to fast for 6-8 hours before blood collection, some patients, especially at outpatients visit, may have failed to follow it, which would affect our laboratory test results.…”
Section: Discussionmentioning
confidence: 99%